Pengaruh Penerapan E-System Pajak Dan Pelayanan Pajak Terhadapa Kepatuhan Wajib Pajak Di KPP Pratama Atambua - Elisa Marlince Seran; Ajat Sudrajat (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aimed to analyze the e-tax system implementation and tax service on taxpayer compliance at Atambua Small Tax Office. This study used a quantitative approach. The analysis used was multiple linear regression analysis and the questionnaires were distributed to 100 respondents. The processing of research data used SPSS 28 software. The results of this study indicated that the e-tax system implementation partially had a positive and significant effect on taxpayer compliance at the Atambua Small Tax Office in 2016-2020 and tax service partially had a positive and significant effect on taxpayer compliance at the Atambua Small Tax Office. Simultaneously, the e-tax system implementation and tax service had a positive and significant effect of 55.1% on taxpayer compliance at the Atambua Small Tax Office.